Pariwisata berkelanjutan melalui Model IAS (Interest, Action, Share) untuk rekonstruksi eduwisata konservasi penyu di Pantai Kili-Kili Trenggalek - Sumarmi Sumarmi; Agung Suprianto; Novika Adi Wibowo; Dicky Arinta; Gracelya Cezia Karamoy; Kelly Yuki Mataru; Natasya Shaherani; Rosniza Aznie Che Rose (Universitas Negeri Malang, 2026)
Sustainable tourism through the IAS (Interest, Action, Share) Model for the reconstruction of sea turtle conservation edutourism at Kili-Kili Beach, Trenggalek This study aims to formulate a strategy for reconstructing sea turtle conservation edu-tourism at Kili-Kili Beach, Trenggalek through the implementation of the IAS (Interest–Action–Share) model as an approach to support sustainable tourism. The identified problems include suboptimal coastal waste management, limited pandanus planting programs as protective habitat vegetation, and insufficient packaging of conservation education for visitors. The research employed a descriptive qualitative approach with the ADDIE framework through field observations, in-depth interviews with managers and tourists, and visual documentation. Data analysis was conducted using Miles and Huberman’s technique comprising data reduction, data display, and conclusion drawing. The results show that the Interest stage successfully attracts tourists through environmental interpretation and digital promotion; the Action stage allows tourists to engage in conservation activities such as beach cleaning and sea turtle release, while the Share stage amplifies conservation messages through social media. However, implementation of the IAS model still faces challenges, particularly limited interpretation facilities, varying levels of ecological literacy, and the need for improved local guide readiness. The study concludes that the IAS model has the potential to enhance tourists’ ecological knowledge and empathy while strengthening local collaboration, although institutional support is required for more sustainable application. These findings indicate opportunities for replication in other coastal conservation destinations with contextual adjustments and are relevant to supporting the achievement of the Sustainable Development Goals (SDGs). Penelitian ini bertujuan merumuskan strategi rekonstruksi eduwisata konservasi penyu di Pantai Kili-Kili, Trenggalek melalui penerapan model IAS (Interest–Action–Share) sebagai pendekatan untuk mendukung pariwisata berkelanjutan. Permasalahan yang diidentifikasi meliputi pengelolaan sampah pesisir yang belum optimal, keterbatasan program penanaman pandan laut sebagai pelindung habitat peneluran, serta minimnya kemasan edukasi konservasi bagi wisatawan. Penelitian menggunakan pendekatan deskriptif kualitatif dengan kerangka ADDIE melalui observasi lapangan, wawancara mendalam dengan pengelola dan wisatawan, serta dokumentasi visual. Analisis data dilakukan dengan teknik Miles dan Huberman melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa tahap interest dapat menarik perhatian wisatawan melalui interpretasi lingkungan dan promosi digital; tahap action memungkinkan wisatawan terlibat dalam kegiatan konservasi seperti bersih pantai dan pelepasan tukik; sedangkan tahap share memperluas jangkauan pesan konservasi melalui media sosial. Meskipun demikian, implementasi model IAS masih menghadapi tantangan berupa keterbatasan fasilitas interpretasi, kesiapan pemandu lokal, serta variasi literasi ekologis pengunjung. Penelitian ini menyimpulkan bahwa model IAS berpotensi meningkatkan pengetahuan dan empati ekologis wisatawan serta memperkuat kolaborasi lokal, namun diperlukan penguatan kelembagaan agar penerapannya lebih berkelanjutan. Temuan ini membuka peluang replikasi di destinasi pesisir lain dengan penyesuaian konteks, sekaligus relevan dalam mendukung capaian Sustainable Development Goals (SDGs).